Case report: Progressive pulmonary artery hypertension in a case of megalencephaly-capillary malformation syndrome - Yoh, Yuri; Shiohama, Tadashi; Uchida, Tomoko; Ebata, Ryota; Kobayashi, Hironobu; Okunushi, Kentaro; Kato, Mitsuhiro; Watanabe, Kazuki; Nakashima, Mitsuko; Saitsu, Hirotomo; Hamada, Hiromichi (Frontiers in Genetics, 2023)
Megalencephaly-capillary malformation syndrome (MCAP, OMIM # 602501) is caused by hyperactivity of the thephosphoinositide-3-kinase (PI3K)-Vakt murine thymoma viral oncogene homolog (AKT)-mammalian target of rapamycin (mTOR) pathway, which results in megalencephaly, capillary malformations, asymmetrical overgrowth, and connective tissue dysplasia. Herein, we report the case of a 7-month-old girl with MCAP due to a PIK3CA somatic mosaic variant who presented with atrial tachycardia, finally diagnosed as pulmonary arterial hypertension (PAH). Oxygen therapy and sildenafil decreased pulmonary blood pressure and improved atrial tachycardia. Previous studies reported an association between the PI3K/AKT/mTOR pathway and abnormal pulmonary arterial smooth muscle cell proliferation, which may be associated with PAH. PAH should be considered a potentially lethal complication in MCAP patients, even when no structural cardiac abnormalities are identified in the neonatal period.